EVALUATION OF THE EFFECTIVENESS OF STRATEGIC PLANNING - Беспаева, Р.; Бугубаева, Р.; Гимранова, Г.; Березюк, В.; Абдикаримова, A. (Journal of Economic Research & Business Administration, 2019)
Strategic planning enables shareholders and company management to determine the direction and pace of business development, outline global market trends, understand what organizational and structural changes must occur in a company in order for it to become competitive, what is its advantage, what tools are necessary for its successful development. In conditions of tough competition and a rapidly changing situation, enterprises should not only focus on the internal state of affairs, but also develop a long-term strategy of behavior that would allow them to follow the changes taking place in their environment. The acceleration of changes in the environment, the emergence of new consumer demands, the updating of business opportunities opened up by the achievements of science and technology, the development of information networks, the availability of modern technologies, the increasing role of human resources, and a number of other factors led to a sharp increase in the importance of strategic management and planning. This article assesses the feasibility of the program-oriented benchmarks of the strategic planning of the tourism industry in Kazakhstan, namely, the Shchuchinsko-Borovskaya resort area of the Republic of Kazakhstan. Based on the methodology for evaluating the effectiveness of strategic planning, a system of interrelations between the program-targeted benchmarks of the strategic planning of the tourism sector in Kazakhstan and the directions of tourist destinations strategies is substantiated. For the most complete assessment of the strategic planning system of the Shchuchinsko-Borovsky resort area, we will analyze strategies at the levels of: republican, regional and business structures and apply the methodology for evaluating the effectiveness of implementing strategies for socio-economic development of levels based on performance evaluations and managing the implementation of strategies that improve efficiency strategic management decisions.